Analisa Manajemen Waktu Pekerjaan Renovasi Pembangunan Cafe Terakota - Al-bab, Ulul; Hepiyanto, Rasio (Jurnal Talenta Sipil, 2024)
Successful execution of a construction project on time is one of the most important goals, for both owners and contractors. As in the construction of terracotta cafee renovation work which regressed to week 14, causing inaccuracies between the planning schedule and the construction implementation schedule. This study aims as an evaluation to get the fastest time acceleration using the CPM (Critical Path Method) cut and crashing method. From schedule data, RAB, and analysis of wage prices and weekly progress, a network is created and determines the critical path to then be cut and crashed. From the results of the study, it was found that the acceleration of the project can be done up to 77 days 6 days faster than normal days, which are 83 days with an acceleration cost of Rp. 337,649,065.79 or an increase of Rp. 20,125,000 from the normal cost of Rp. 317,524,065.79. The percentage of comparison due to the acceleration of the project using the critis cut and crash path method, that is, for an acceleration time of 5.59% faster than normal time. Meanwhile, the acceleration fee is 6.34% greater than the normal cost. So with this research, the costs incurred become more expensive, but the project completion time becomes shorter and more concise. It done on July 2rd, 2023.